Penatalaksanaan Fisioterapi Dada dan Pemberian Rebusan Jahe Merah Dengan Masalah Keperawatan Ketidakefektifan Bersihan Jalan Nafas Pada Pasien Asma Bronkiale Di Desa Singodutan - Oriza Tiarismi Qufita Resti; Deden Dermawan (Unit Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Bhakti Mulial, 2022)
: Asthma is a condition in which the airways narrow due to hyperactivity to certain stimuli. Symptoms are shortness of breath and coughing up phlegm that is difficult to expel so that airway clearance is not effective. Efforts that can be made to overcome the problem of ineffective airway clearance are chest physiotherapy and red ginger decoction. This study was to describe chest physiotherapy and administration of red ginger decoction with nursing problems of ineffective airway clearance in bronchial asthma patients. The type of research is a qualitative research with a case study approach to the nursing process. The technique of taking research subjects with non-probability sampling purposive sampling approach. The study data on the subject obtained shortness of breath and coughing up phlegm that was difficult to expel, restless, anxious, and difficult to expel sputum, irregular breathing rhythm, rapid and shallow depth of breath, using accessory muscles of respiration, chest expansion is not maximal, there is a dull sound, there is a buildup of secretions in the right and left bronchi, and there is a sound additional rhonchi. Nursing diagnosis is ineffective airway clearance. Action plan for giving chest physiotherapy and red ginger decoction. Implementation of nursing by giving chest physiotherapy and red ginger decoction for 6 times. Evaluation of the three subjects said that shortness of breath was reduced and secretions could be removed. The amount of secretions is about 7 – 8 cc and clear white secretions, Breathing: 20 times per minute. Chest physiotherapy and administration of red ginger decoction are effective to overcome the problem of ineffective airway clearance.